The Organizational Silence of the Educational Supervisors and Physical Education Specialist in Iraq - Ouday Gh. Al-Qawaz (College of Physical Education and Sport Sciences, 2021)
The research aims to identify the dimensions of organizational silence and its factors for educational supervisors and supervisors with specialization (physical education specialization). The researchers used the descriptive analytical method. The organizational silence questionnaire was approved for (Zainab Abdel Razzaq  Abboud, and Zafar Nasser Hussain, 2016) for the organizational silence applied to a sample of employees at the Presidency of the University of Babylon in Iraq, in obtaining the necessary data, and the research sample consisted of (111) educational supervisors and specialists from the followers For the Directorate of Educational Supervision in Iraq, frequency and percentage were used in extracting the levels of response to the measures as statistical methods. The researchers concluded that there is a low organizational silence among educational supervisors in the Directorate of Educational Supervision in Iraq , except  administrative and organizational reasons where silence is average.